2018
DOI: 10.1063/1.5030524
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and decomposition mechanisms of SF6 at different partial discharge determined by infrared spectroscopy

Abstract: Probing the decomposition products of Sulfur hexafluoride (SF6) under partial discharge provides important information for fault diagnosis of Gas Insulated Switchgear (GIS). Here, the effects of discharging time, gas pressure, and discharging voltage on SF6 decomposition products have been investigated by Fourier transform infrared (FTIR) spectroscopy. The infrared spectra of decomposition products such as CF4, SOF2, and SO2F2 have been obtained. It can be found that the CF4, SOF2, and SO2F2 concentrations inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The decomposition of SF 6 courses with the breaking of S-F chemical bonds and the fractured bond number is proportional to the discharge energy. Although more energy is required for breaking S-F bonds, SF 4 and SF 2 are the main decomposition products of SF 6 , because they are more stable than SF 5 and SF 3 with their symmetrical structure. The SF 5 , SF 3 , SF products are easy to combine with the free F atoms, so they are not stable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposition of SF 6 courses with the breaking of S-F chemical bonds and the fractured bond number is proportional to the discharge energy. Although more energy is required for breaking S-F bonds, SF 4 and SF 2 are the main decomposition products of SF 6 , because they are more stable than SF 5 and SF 3 with their symmetrical structure. The SF 5 , SF 3 , SF products are easy to combine with the free F atoms, so they are not stable.…”
Section: Methodsmentioning
confidence: 99%
“…One of the key parameters for effectively evaluating the discharge fault is the SF 6 decomposed components. Many detection techniques have been applied to the analysis of SF 6 decomposition products, such as gas chromatography, gas detection tubes, electrochemical methods, and spectral methods 5 . Moreover, various decomposition components, such as CF 4 , CO 2 , SOF 2 , and SO 2 F 2 , can effectively reflect the severity of the discharge fault and the type of insulation defects 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In GIS, PD is considered an indicator of dielectric's degradation and the initial cause of the deterioration rate's acceleration. The types and concentrations of decomposition components are strongly affected by defect severity, applied voltage, discharge duration, and gas pressure [54]. Despite its low energy compared to arc and spark discharges, and its low discharge current in the order of microamps, PD represent 85% of causes of GIS catastrophic failures.…”
Section: E Sf6 Decomposition By Partial Dischargementioning
confidence: 99%
“…The relationship between decomposition products and PD conditions has been investigated using the chemical detection method. For instance, in [54], the optical properties of the decomposition products have been evaluated using FTIR under different PD conditions. It's found that the content of CF4, SOF2, and SO2F2 has increased along the discharge period.…”
Section: ) Pd Analysis Based On Decomposed Component Analysis (Dca)mentioning
confidence: 99%
“…Colorimetric sensors have also been used, utilizing radical reactions of cobalt ions, 40 chemical bonding, 41 and induction of amine‐based reactivity 42 . More recently, various portable gas sensors have been developed and commercialized using chromatography and infrared spectroscopy techniques to analyze SO 2 gas in a GIS 43,44 . However, these methods are not suitable for real‐time monitoring of SF 6 decomposition by‐products' properties, as they are relatively expensive, destructive, require long sampling or response times, and lack consideration of specificity within GIS.…”
Section: Introductionmentioning
confidence: 99%